Standardized Treatment and Shortened Depression Course can Reduce Cognitive Impairment in Adolescents With Depression - Cao, Penghui; Tan, Junjie; Liao, Xuezhen; Wang, Jinwei; Chen, Lihuan; Fang, Ziyan; Pan, Nannan (Journal of korean Academy of Child and Adolescent Psychiatry, 2024)
This study aimed to explore the influence of depression severity, disease course, treatment status, and other factors on cognitive function in adolescents with depressive disorders. Participants who met the inclusion criteria were enrolled in the study. Sociodemographic data of each participant were recorded, including age, sex, and family history of mental disorders. Zung's Self-Rating Depression Scale was used to assess depression status in adolescents. Moreover, P300 and mismatch negativity (MMN) were used to objectively evaluate the participants' cognitive function. Only 26.8% of the adolescents with depression received standard antidepressant treatment. The latencies of N2 (267.80±23.34 ms), P3 (357.71±32.09 ms), and MMN (212.10±15.61 ms) in the adolescent depression group were longer than those in the healthy control group (p<0.01). Further analysis revealed that the latency of MMN was extended with increased levels of depression in adolescents. The MMN latency was short in participants with depression receiving standardized treatment. Furthermore, the latency of MMN was positively correlated with the severity and duration of depression (correlation coefficients were 0.465 and 0.479, respectively) (p<0.01). Receiving standardized treatment and shortening the course of depression can reduce cognitive impairment in adolescents with depression.